Multilocus typing sequences in Lactobacillus casei isolates from pineapple peels silages - WingChing Jones, Rodolfo (2021)
Introduction. Lactobacillus casei is characterized by adapting to the environment during the fermentation process. Objective. To characterize with multilocus typing sequences (MTLS) isolates of L. casei present in pineapple peel silage with increasing levels of urea. Materials and methods. During 2017 and using an unrestricted random design, twenty silos (2 kg) were prepared. Every five bags, 0, 0.5, 1 and 1.5 % urea (w/w on fresh basis) were added. After thirty days, a sample was taken from each repetition for bromatological analysis. Dry matter (DM), crude protein (PC), non-fibrous carbohydrates, fiber in acid detergent (ADF), fiber in neutral detergent (NDF), in vitro digestibility of dry matter (IVDDM), hemicellulose, ethereal extract (EE), ashes, ammonia nitrogen, and pH. The Lactic Acid Bacteria (LAB) count was determined for each one of the treatments. Identification of LABs was carried out using the 16S rRNA sequence. The isolates of L. casei were analyzed using MTLS. Results. The four evaluated treatments did not present significant differences in DM (12.10 to 12.86 %), ADF (31.44 to 32.18 %), NDF (58.46 to 58.56 %), hemicellulose (26.36 to 27.02 %), EE (2.45 to 2.96 %), ash (4.96 to 5.12 %), ammonia nitrogen (0.45 to 0.49 %) and pH (3.36 at 3.48). Not so, in CP (6.94 to 9.12 %), and IVDDMS (82.84 to 84.72 %). The addition of urea was associated with changes in the BAL populations (6.56 to 6.90 CFU). Seven isolates of L. casei were identified and typed with five different genes. Between two (polA) and five (nrdD, pgm, mutL) alleles were found. This allowed the identification of a total of six different type sequences (ST) in the Costa Rican isolates. Conclusion. The L. casei isolates were found to be related to bacteria from the gastrointestinal tract in humans.